UsingRole-playingTechniqueto EnhanceLearners’Cultural Competence.ThecaseofSecondYearEFLlearnersatAbdAlMajid Mezianesecondaryschool - Guechi Wassila, Souilah Safia (My University, 2019)
Abstract: Thepresentstudyattemptstoinvestigatethefactofenhancinglearners’ culturalcompetencethroughtheuseofrole-playtechnique.Theparticipants of thisstudyareSecondYearLiteratureandForeignLanguagesatAbdAlMajid Mezianesecondaryschool.Itwasnoticeablethatlearnersfaceproblemsin differentsocialandculturalsituationswheretheyshouldspeakandact appropriately;theyareknowledgeablebuttheyareunabletopracticethis knowledgeinreallifesituations.Toachieveouraimsforthisstudy,the descriptivemethodischosen.Dataarecollectedthrougha mixed methodologybasedonqualitativeandquantitativemethods.Wehaveuseda classroomobservationasqualitativemethodwhereasaquestionnaireis chosenasaquantitativeone.Theresultsfromtheanalysisofthe questionnaireandthedescriptionofclassroomobservationhaveshownthat learnersweresomotivatedtolearnusingsuchtechniqueintheirclasses. Thus,werecommendEFLteacherstousethistechniqueintheirclassesto motivate learners andto help themincrease their level in English,especiallyits appropriate use in differenttargetsituations.
Keywords: Keywords: Role-plays, EFL learners,cultural competence.